Determinants Of Land And Building Tax Payer Compliance With Applicable Laws - jumaiyah jumaiyah; Risa Ardianti; Wahidullah Wahidullah (Accounting Study Program, Faculty of Economics and Business, 2022)
One of the potential sources of money for regional income is the tax on land and buildings in both rural and urban areas. Land and construction tax P2 is a possible source of funding for regional financing, but because taxpayer compliance is relatively low, the reality of tax collection is still extremely challenging for the regions. The purpose of this study is to investigate how tax payer compliance among rural and urban land and building taxpayers is influenced by tax payer awareness, tax knowledge, tax penalties, and tax collection services. Using the convenience sampling approach, a sample of 100 respondents from rural and urban land and building taxpayers in Guyangan Village represented the population of this study, which included land and building taxpayers in both rural and urban locations. Primary data are used.